Awareness and Use of Social Media for Research Activities among Library and Information Science Postgraduate Students in Public and Private Universities in Southwest Nigeria - Sodipe, Oluseun Mobolanle; Abdullah, Fauziyah Olayinka; Ibeachusim, John Echesirim IBEACHUSIM; Adeleye, Rashidat Adepeju (Communicate: Journal of Library and Information Science, 2025)
This study examined the awareness and use of social media for research activities among library and information science postgraduate students in public and private universities, in South-West, Nigeria. A descriptive survey research design was adopted for this study. A total enumeration sampling technique was adopted to select 175 respondents. The instrument for data collection was a self-constructed questionnaire. The data analysis was subjected to descriptive statistics (frequency, percentage, mean, and standard deviation). Findings revealed that there is a high level of awareness of social media for research; there is a high level of utilization of Social Media for research activities among LIS postgraduate students and the result is favorable to Google+, Facebook, YouTube, Wikis, ResearchGate, Academia, ScienceStage, LinkedIn, Twitter and Blog. The major reasons for the preference of using social media for research activities among LIS postgraduate students are to provide them with links to other sites/resources they can use for research; sharing research information is more convenient on social media. The major challenges faced by the LIS postgraduate students in using social media for research activities are lack of institutional support, low quality of shared content, and security issues. Based on the findings, it was therefore recommended that institutional support be provided for using social media for academic/research purposes. Social media conferences and workshops should be organized for LIS postgraduate students at all levels especially those in the university on how to integrate social media tools, platforms, and other internet tools into their academic/research lives